Engaging K-8 Students through Inquiry-based Learning and School Farms. Issue 1 (2nd January 2019) - Fifolt, Matthew; Morgan, Amy F.
Abstract: Student engagement in under-resourced public schools remains an ongoing challenge in the United States. Moreover, there is no panacea for student disengagement in high poverty urban schools. However, experts have suggested that appropriate interventions for early and middle grade students can increase motivation and interest and promote a growth mindset. The purpose of this case study was to explore principal and teacher experiences with Jones Valley Teaching Farm (JVTF), a Birmingham-based 501 (c)(3) nonprofit that uses a hands-on food education model to teach academic standards-based lessons via onsite school farms and school-embedded JVTF instructors. The research team used a descriptive case study method to conduct semi-structured interviews with principals (n = 5) and focus group interviews with classroom teachers (n = 15). Participants viewed JVTF as a catalyst for student engagement and a model that has great potential for contributing to the retention of students at high risk of dropping out of school.